Impact of VSC faults on dynamic performance and low voltage ridethrough of DFIG - Abdou, A.; Abu-Siada, Ahmed; Pota, H. (Elsevier Ltd, 2015)
A doubly-fed induction generator’s (DFIG’s) sensitivity to external faults has motivated researchers to investigate the impact of various grid disturbances, such as voltage sags and short circuit faults, on its low-voltage ride-through (LVRT) capability. However, no attention has been paid to the impact of internal faults in voltage source converters (VSCs) that interface a DFIG with the grid, on the dynamic performance of the machine. This paper investigates the impacts of various VSC faults, on the dynamic performance and LVRT capability of a DFIG. Faults such as open and short circuit within VSC switches and across the DC-link capacitor are considered in this paper. The impact of internal VSC faults when they occur within the grid side converter (GSC) and rotor side converter (RSC) is investigated. Compliance of the voltage profiles of a DFIG with the LVRTs specified in the recent grid codes of the USA, Spain, Mexico, Denmark, Ireland, Germany, Quebec and the UK are examined for the faults studied. The simulation results show that these faults should be considered in designs of protection systems aimed at avoiding any catastrophic failure of the converter switches or wind turbine.